2012
DOI: 10.5539/jas.v4n2p101
|View full text |Cite
|
Sign up to set email alerts
|

Infection Process of Olive Fruits by Colletotrichum acutatum and the Protective Role of the Cuticle and Epidermis

Abstract: Colletotrichum acutatum is a serious concern for the Portuguese oliviculture and food industry, due to both olive oil yield and quality decrease. While the organism's phytopathogenic potential has been well documented, the pathogen adhesion and colonization process in olives remain poorly understood. This paper reports experiments conducted on C. acutatum-susceptible, C. acutatum-moderately resistant and C. acutatum-resistant olive fruits during infection process, in two consecutively years, to identify the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
(34 reference statements)
2
15
0
Order By: Relevance
“…This corroborates field experience of high anthracnose susceptibility of 'Maçanilha de Tavira' and 'Galega Vulgar', and of resistance attributed to 'Blanqueta', 'Negrinha de Freixo' and 'Picual' (Mateo-Sagasta 1968;Leitão et al 1986;Moral et al 2008;Gomes et al 2012). 'Cordovil de Serpa' revealed an intermediate behaviour.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This corroborates field experience of high anthracnose susceptibility of 'Maçanilha de Tavira' and 'Galega Vulgar', and of resistance attributed to 'Blanqueta', 'Negrinha de Freixo' and 'Picual' (Mateo-Sagasta 1968;Leitão et al 1986;Moral et al 2008;Gomes et al 2012). 'Cordovil de Serpa' revealed an intermediate behaviour.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, the analysis of the correlation between disease severity and either conidia germination or appressoria formation revealed that the final outcome of the disease severity was, in part (up to 30 %), due to the initial hostpathogen recognition events. No differences could be detected in the histopathological comparison of the infection processes between compatible and incompatible interactions (Gomes et al 2012). However, present results suggest that specific recognition events may be occurring at an early stage, conditioning spore germination and appressorium formation, which in turn can condition the disease severity.…”
Section: Discussionmentioning
confidence: 52%
“…Once penetration succeeds, the pathogen colonizes the host cells, which then become densely infected, and finally necrotic lesions and hyphae become visible (Gomes et al, 2012). Secondary hyphae grow extensively inter-and intracellularly across cell walls.…”
Section: Symptoms Of Chili Anthracnose and Colletotrichum Lifestylesmentioning
confidence: 99%
“…Moreover, in numerous plants, the formation of a thicker cuticle also occurs as a protection to cold-induced winter drought [53]. Leaf and fruit cuticles generally contain the same classes of compounds, however, genotype-specific-changes are possible, as, in fact, occurs in olive trees in response to drought and pathogens [52,54]. In a previous paragraph, it has been shown that cutinosomes, enriched in C18:2-FA, are extruded by the seed coat to the endosperm to cause an indirect protection for desiccation to the non-cutinised embryo, with osmotin involved in this lipid-trafficking (Figure 2I).…”
Section: Oefad8 Expression Is a Determinant For Cold-acclimation Imentioning
confidence: 99%